(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Mucoadhesive microcapsules of indomethacin were prepared by an emulsification-ionic gelation process employing sodium carboxy methylcellulose, methylcellulose, Carbopol and hydroxy propyl methyl cellulose along with alginate and the microcapsules were evaluated for release kinetics and ulcerogenic activity. The resulting microcapsules were discrete, free flowing, multinucleate, monolithic and spherical. Microencapsulation efficiency was 41-70 % and relatively high with alginate-sodium carboxymethylcellulose. Indomethacin release from these mucoadhesive microcapsules was found to be slow and extended over longer periods of time and depended on the composition of coat and size of the microcapsules. Drug release was diffusion controlled and followed first order kinetics. Alginate-methyl cellulose and alginate-sodium carboxymethylcellulose microcapsules were found suitable for oral controlled release. The microcapsules exhibited good mucoadhesive property in the in vitro wash-off test. Release from some microcapsules fulfilled the official (USP 23) drug release test-2 requirement of indomethacin extended release capsules. A 62-80 % reduction in ulcerogenic activity was observed with these microcapsules when compared to pure drug indomethacin.